PENGALAMAN KOMUNIKASI PEKERJA STARTUP PADA PRAKTIK HUSTLE CULTURE - Galuh Aulia Ramadhanti; Jasmin Jannatania; Deffri Ihza Adiyanto; Shinta Qayla Vashty (Ilmu Komunikasi, FISIP Universitas Pasundan, 2022)
ABSTRACT As a start-up company, startups adhere to a flexible work system and have less stringent regulations, so that they are preferred by the younger generation. On the other hand, challenges and high work demands sometimes overwhelm workers and create a hustle culture. This study aims to understand how the phenomenon of hustle culture is interpreted by startup workers, as well as explore the communication experience for startup workers in the practice of hustle culture. This study uses a qualitative method with a phenomenological study approach. Two theories used as the basis in this research include the theory of symbolic interaction and the theory of cognitive dissonance. The data was obtained through interviews with 4 informants who are permanent employees of startup companies and also experience hustle culture. Based on the results of the study, it was found that startup workers interpret hustle culture as self-evident behavior, seeking feelings of satisfaction and pride, as well as a success factor. Hustle behavior is also influenced by the work environment and company targets. Meanwhile, the communication experiences experienced by startup work are feeling short of time, declining health conditions, and toxic productivity